Organization Structure Development Based On Company Business Process - Ferry Hariawan (UII, 2017)
Organizational structure is one way for companies to manage human resources owned efficiently. With the organizational structure, it is expected to increase the awareness and commitment of employees in order to provide optimal work performance. Preparation of organizational structure within the company generally carried out without regard to business processes that occur, consequently the efficiency of human resources is not implemented. The business process is a set of structured or interdependent work or literature to solve a problem or to produce a product or service (to achieve a particular goal). Business processes can be broken down into several subprocesses that each process has its own attributes but also contributes to achieve a goal of its subprocess.